Offering Psychological Support to University Students in Poland During the COVID-19 Pandemic: Lessons Learned From an Initial Evaluation - Rudnik, Agata; Anikiej-Wiczenbach, Paulina; Szulman-Wardal, Aleksandra; Conway, Paul; Bidzan, Mariola (Frontiers in Psychology, 2021)
This perspective article aims to present insights into an initiative to provide free psychological support to students at the University of Gdańsk (UG) – one of the first universities in Poland to offer such help – during the first major COVID-19 pandemic lockdown in March 2020. We begin by introducing key psychological consequences of the pandemic, with particular emphasis on university students, according to Pandemic Management Theory (PMT). Next, we highlight the most significant challenges reported to us by the students in response to the support initiative and applied psychological interventions (including psychoeducation, relaxation, arranging day plans, taking care of relationships, and “just” talking). We conclude by reflecting on the challenges for mental health posed by the COVID-19 pandemic as well as the outcome of our initiative – the creation of the Academic Psychological Support Centre at the University of Gdańsk. These insights and lessons learned from developing our practice can help enhance the effectiveness of future psychological support programmes through the pandemic and beyond.